Uczenie się w perspektywie św. Tomasza z Akwinu i neurobiologii – dysharmonicznie czy unisono? - Michał Nowicki, Michał Nowicki; Kowalska, Klaudia (Studia Edukacyjne, 2016)
In this article, we review the pedagogical ideas of St. Thomas Aquinas, as well as the assumptions of neurogenesis, synapsogenesis and mindfulness and their utility in educational directives. Our aim is to verify whether these both positions are consistent. The end result is to specify the character of teacher, which will consent with St. Thomas’ and neurobiologists ideas.